High-resolution visualization and quantification of nucleic acid–based therapeutics in cells and tissues using Nanoscale secondary ion mass spectrometry (NanoSIMS). Issue 1 (4th December 2020) - He, Cuiwen; Migawa, Michael T; Chen, Kai; Weston, Thomas A; Tanowitz, Michael; Song, Wenxin; Guagliardo, Paul; Iyer, K Swaminathan; Bennett, C Frank; Fong, Loren G; Seth, Punit P; Young, Stephen G; et al.
Abstract: Nucleic acid therapeutics (NATs) have proven useful in promoting the degradation of specific transcripts, modifying gene expression, and regulating mRNA splicing. In each situation, efficient delivery of nucleic acids to cells, tissues and intracellular compartments is crucial—both for optimizing efficacy and reducing side effects. Despite successes in NATs, our understanding of their cellular uptake and distribution in tissues is limited. Current methods have yielded insights into distribution of NATs within cells and tissues, but the sensitivity and resolution of these approaches are limited. Here, we show that nanoscale secondary ion mass spectrometry (NanoSIMS) imaging can be used to define the distribution of 5-bromo-2′-deoxythymidine (5-BrdT) modified antisense oligonucleotides (ASO) in cells and tissues with high sensitivity and spatial resolution. This approach makes it possible to define ASO uptake and distribution in different subcellular compartments and to quantify the impact of targeting ligands designed to promote ASO uptake by cells. Our studies showed that phosphorothioate ASOs are associated with filopodia and the inner nuclear membrane in cultured cells, and also revealed substantial cellular and subcellular heterogeneity of ASO uptake in mouse tissues. NanoSIMS imaging represents a significant advance in visualizing uptake and distribution of NATs; this approach will be useful in optimizing efficacy and delivery of NATs for treating human disease.